2009
DOI: 10.1021/jp810502v
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution and Dispersed Fluorescence Examination of Vibronic Bands of Tryptamine: Spectroscopic Signatures for La/Lb Mixing near a Conical Intersection

Abstract: The vibronic spectrum of tryptamine has been studied in a molecular beam up to an energy of 930 cm(-1) above the S(0)-S(1) electronic origin. Rotationally resolved electronic spectra reveal a rotation of the transition dipole moment direction from (1)L(b) to (1)L(a) beginning about 400 cm(-1) above the (1)L(b) origin. In this region, vibronic bands which appear as single bands at low resolution contain rotational structure from more than one vibronic transition. The number of these transitions closely tracks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…3͒. This is very different from the cases of indole 17,18 and tryptamine, 39 where strong vibronic mixing significantly affects both the intensities and the band type of many vibronic bands. Also the band type, which reflects the orientation of the transition dipole moment, is practically the same in the FC and the FCHT approximation.…”
Section: B Calculated Vibrational and Vibronic Spectramentioning
confidence: 85%
“…3͒. This is very different from the cases of indole 17,18 and tryptamine, 39 where strong vibronic mixing significantly affects both the intensities and the band type of many vibronic bands. Also the band type, which reflects the orientation of the transition dipole moment, is practically the same in the FC and the FCHT approximation.…”
Section: B Calculated Vibrational and Vibronic Spectramentioning
confidence: 85%
“…Both theoretical studies and measurements on indoles in van der Waals clusters have found evidence of 1 L a / 1 L b mixing. Gas phase geometrical parameters for the ground and 1 L a / 1 L b excited states of 5‐hydroxyindole have been calculated at the CASSCF and TDDFT levels of theory, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Emission from 1 L a is difficult to rule out because the energetic position of the 1 L a origin remains unknown, and is hidden by overlap with the 1 L b transition. Various spectroscopic techniques , theoretical calculations and tryptophan model compounds have been applied to resolve this conundrum.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 L a (S 2 ) state in polar environments lies below the 1 L b (S 1 ) state due to its larger static dipole moment. 12 Ultrafast internal conversion through conical intersection (CI) was proposed from the higher 1 L b to lower 1 L a state 13-15 and observed to occur in ~40 fs in bulk water. 16,17 The internal conversion from 1 L a to 1 L b in gas phase (or in vacuum) has also been observed in 20-100 fs.…”
mentioning
confidence: 99%
“…Note that fa/fba indicates the difference of emission coefficients of the initial excited 1 L a state and the transferred 1 L a state at the same emission wavelength (310 or 335 nm), reflecting that the emission at the same wavelength could be from the different vibronic 1 L a states and that the transferred 1 L a is not at the same energy level of the initial excited 1 L a state, consistent with the CI mechanism. 13-15 …”
mentioning
confidence: 99%